1999
DOI: 10.1038/sj.ijo.0801053
|View full text |Cite
|
Sign up to set email alerts
|

Body size and composition in Polynesians

Abstract: OBJECTIVES: To compare the relationship between body size and body composition in New Zealanders of Polynesian and European descent and to develop speci®c regression equations for fat mass for Polynesians. SUBJECTS: 189 Maori (93 males, 96 females), 185 Samoans (88 males, 97 females) and 241 Europeans (89 males, 152 females) aged 20 ± 70 y. MEASUREMENTS: Height, weight, four skinfold thicknesses, bioelectrical impedance analysis (BIA) and dual energy X-ray absorptiometry (DXA). RESULTS: At higher body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
160
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 13 publications
(7 reference statements)
7
160
1
Order By: Relevance
“…Participants with a ratio of energy intake to estimated resting metabolic rate (EI:RMR est ) of <0·9 were classified as low energy reporters. The method used to identify low energy reporters was consistent with that used by Pikholz et al (8) and Gemming et al (9) , with specific equations from Swinburn et al used for NZ Māori and Pacific ethnic groups to estimate fat mass from BMI and RMR est (10) . Participants with incomplete data for weight and height, and those of non-European ethnicity within the derived NZ European and Others ethnic group were excluded from the sensitivity analysis.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…Participants with a ratio of energy intake to estimated resting metabolic rate (EI:RMR est ) of <0·9 were classified as low energy reporters. The method used to identify low energy reporters was consistent with that used by Pikholz et al (8) and Gemming et al (9) , with specific equations from Swinburn et al used for NZ Māori and Pacific ethnic groups to estimate fat mass from BMI and RMR est (10) . Participants with incomplete data for weight and height, and those of non-European ethnicity within the derived NZ European and Others ethnic group were excluded from the sensitivity analysis.…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…However, there is increasing evidence suggesting that this cut-off value cannot be applied to nonCaucasian populations, e.g. Asian or Pacific island populations (Swinburn et al, 1999; WHO/IASO/IOTF, 2000; Ko et al, 2001). Conventional BMI cut-offs would underestimate the prevalence of obesity for Asian populations, but overestimate it for Pacific island populations.…”
Section: Introductionmentioning
confidence: 99%
“…21 Another study showed that, at higher BMI levels, Polynesians had significantly more lean mass than Europeans. 22 Another possible explanation is that, as Polynesians in New Caledonia are generally employed in heavy, energy-consuming work, this may significantly enhance their insulin sensitivity. 4,23 Also, it cannot be excluded that Polynesians have an insulin-deficient form of diabetes, different from type 2.…”
mentioning
confidence: 99%